SHAXSNING IJTIMOIYLASHUV OMILLARI VA UNING ETNOPSIXOLOGIK JIHATLARI. (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article examines the specific aspects of the ethnopsychological characteristics of a person in interpersonal relationships and the process of socialization in the relationships taking place in relation to her. It is known that a child is not born choosing his homeland or parents. So he is not even born with the ready-made mental characteristics inherent in his nationality. This article examines the specific aspects of the ethnopsychological characteristics of a personality in interpersonal relationships and the process of socialization in the relationships taking place in relation to it. It is known that a child is not born choosing his homeland or parents. So he's not even born with the mental characteristics inherent in him.